2020
DOI: 10.1007/s11837-020-04072-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Solidified Industrial Copper Matte and Fayalite Slag

Abstract: The thermal conductivity of various copper matte and fayalite slag was measured using laser flash analysis, a non-steady state measurement method. Industrial matte and slag samples were taken in such a way that their composition represented typical process conditions. Thermal conductivities for solid copper matte (average 64 % Cu) were found to be from 1.2 W m -1 K -1 at 300 °C to 2.1 W m -1 K -1 at 900 °C. Because arsenic is one of the most important impurities in copper matte, its effect on thermal conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Large slag particles have cracks that formed during the fast quenching in the water jet. The formation of the cracks is attributed to the low thermal conductivity of the slag [ 41 , 42 , 43 , 44 ] and the difference in coefficients of thermal expansion, thus shrinkage, between the slag and the matte (metal) phases, which result in thermal stresses inside the solidified material. The particle size distribution in Figure 2 suggested that the materials of granulometric size larger than 300 µm represent about 90% ( w / w ) of the sample of the received historic slag material.…”
Section: Resultsmentioning
confidence: 99%
“…Large slag particles have cracks that formed during the fast quenching in the water jet. The formation of the cracks is attributed to the low thermal conductivity of the slag [ 41 , 42 , 43 , 44 ] and the difference in coefficients of thermal expansion, thus shrinkage, between the slag and the matte (metal) phases, which result in thermal stresses inside the solidified material. The particle size distribution in Figure 2 suggested that the materials of granulometric size larger than 300 µm represent about 90% ( w / w ) of the sample of the received historic slag material.…”
Section: Resultsmentioning
confidence: 99%
“…During the industrial flash smelting process, the slag and flue gas carry 16% and 29% of the heat from the reactions in the furnace, respectively (Kojo and Storch, 2006). If the slag output reaches 40 million metric tons in 2020 (Meng et al, 2020) and considering the specific heat of copper slag C ps =1100 J/kg• K (Sibarani et al, 2020;Xia et al, 2007), it can be calculated that the total thermal energy carried by molten slags is equivalent to the combustion heat of 3.3 Mt of standard coal, meanwhile the flue gas total thermal energy equals to 6.0 Mt of standard coal. With the theoretical recoveries 95.8% and 91.8%, and 81.6% of Ni, Co, and Cu respectively, J o u r n a l P r e -p r o o f using the contents in the smelting slag analyzed in this study, the amounts of these recovered metals can reach 0.39 Mt Cu, 0.019 Mt Ni and 0.022 Mt Co every year from the flash smelting slag.…”
Section: Prospects For Industrial Applicationmentioning
confidence: 99%